Advancing Creativity Theory and Research : A Socio-cultural Manifesto (2019)
ABSTRACT: This manifesto, discussed by 20 scholars, representing diverse lines of creativity research, marks a conceptual shift within the field. Socio-cultural approaches have made substantial contributions to the concept of creativity over recent decades and today can provide a set of propositions to guide our understanding of past research and to generate new directions of inquiry and practice. These propositions are urgently needed in response to the transition from the Information Society to the Post-Information Society. Through the propositions outlined here, we aim to build common ground and invite the community of creativity researchers and practitioners to reflect up, study, and cultivate creativity as a socio-cultural phenomenon.